Analytical Study of Outpatient Satisfaction in Labuang Baji Regional Public Hospital Makassar - Badwi, Adam; Doken, Stefanus Ama; Alim, Andi; A, Adhyatma (Journal of Global Research in Public Health, 2019)
Background: Patient satisfaction is an indicator of success in providing public health services. Based on the medical record data of Labuang Baji Regional Public Hospital Makassar in 2015-2017 the level of visitors in 2015 was 3,369 patients, in 2016 there were 2,632 patients, in 2017 it decreased to 925 patients. Purpose: The purpose of this study was to determine the relationship between the attitude of the officers, health facilities and patient waiting time with patient satisfaction towards health services in the Labuang Baji Regional Public Hospital Makassar in 2019. Method: This research uses analytic research with cross-sectional study approach with a sample of 265 people with a simple random sampling technique. While the population in this study were all patients who visited the outpatient unit at the Labuang Baji Regional Public Hospital in Makassar. This research was conducted at the Labuang Baji Public Hospital Makassar in August-September 2019. Results: The results showed that the p-value = 0.096> α 0.05 and p-value = 0.862> α 0.05 this meant that there was no relationship between the attitude of the officers and the availability of health facilities with the satisfaction of outpatients in health services at the Labuang Baji Regional Public Hospital Makassar. Meanwhile, for the waiting time, the p-value = 0.027 <α 0.05 indicates that there is a relationship between waiting time and outpatient satisfaction with health services at the Labuang Baji Regional Public Hospital in Makassar. Conclusion: Based on the results described above, it is recommended to the hospital to maintain the quality of service and continue to strive to continuously improve the quality of health care so that patients continue to feel satisfaction.